Four-Element Wideband Circularly Polarized Sequentially-Rotated Slot Antenna Array for Small Spacecraft Technology - Supreeyatitikul, Nathapat; Lertwiriyaprapa, Titipong; Phongcharoenpanich, Chuwong (My University, 2023)
This research proposes four-element wideband circularly polarized (CP) sequentially-rotated slot antenna array. The proposed four-element CP sequentially-rotated slot antenna array consists of four-element C-shaped monopole patch on the upper-layer substrate and octagonal-shaped ring slot ground plane with sequentially-rotated feed network on the lower-layer substrate. The sequentially-rotated feed network is utilized to improve the-10-dB IBW and 3-dB ARBW. The results of the measured IBW and ARBW at 2.4 GHz are 90.41% (1.83-4 GHz) and 85% (1.96-4 GHz), respectively. The maximum gain at 3.3 GHz is 7.8 dBic with bi-directional CP radiation.
Keywords: Antenna array; bi-directional; circularly polarized; monopole; sequentially-rotated feed network